2017
DOI: 10.1186/s12962-017-0064-9
|View full text |Cite
|
Sign up to set email alerts
|

Economic evaluation of participatory learning and action with women’s groups facilitated by Accredited Social Health Activists to improve birth outcomes in rural eastern India

Abstract: BackgroundNeonatal mortality remains unacceptably high in many low and middle-income countries, including India. A community mobilisation intervention using participatory learning and action with women’s groups facilitated by Accredited Social Health Activists (ASHAs) was conducted to improve maternal and newborn health. The intervention was evaluated through a cluster-randomised controlled trial conducted in Jharkhand and Odisha, eastern India. This aims to assess the cost-effectiveness this intervention.Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 20 publications
0
28
0
Order By: Relevance
“…Without such information, the policy implications of studies examining the impact of women’s groups operating at scale will remain unclear. While various studies examine the costs and cost-effectiveness of women’s groups aiming to improve health outcomes ( Mangham-Jefferies et al, 2014 , Colbourn et al, 2015 , Sinha et al, 2017 , Pulkki- Brännström et al, 2020 ), somewhat paradoxically there is limited information on the costs of women’s groups with economic objectives.…”
Section: Introductionmentioning
confidence: 99%
“…Without such information, the policy implications of studies examining the impact of women’s groups operating at scale will remain unclear. While various studies examine the costs and cost-effectiveness of women’s groups aiming to improve health outcomes ( Mangham-Jefferies et al, 2014 , Colbourn et al, 2015 , Sinha et al, 2017 , Pulkki- Brännström et al, 2020 ), somewhat paradoxically there is limited information on the costs of women’s groups with economic objectives.…”
Section: Introductionmentioning
confidence: 99%
“…The incremental cost-effectiveness ratio of $INT41 is substantially lower than India’s GDP per capita (ranging from 0.3% to 7% of GDP). FLAG’s ICER is 85% lower than that found in a smaller-scale efficacy trial of women’s groups facilitated by ASHAs conducted in Jharkhand and Odisha (ICER of 2017 INT$ 274 or US$83), and 70% lower than in another smaller trial of women’s groups supported by salaried facilitators in the same states (ICER of 2016 INT$ 135) [13] [12]. Similarly, FLAG’s ICER is also substantially lower than those reported for small scale efficacy trials of women’s groups in Nepal, Bangladesh, and Malawi[12] (Table S2).…”
Section: Discussionmentioning
confidence: 84%
“… 43 44 The ICERs estimated in this study were substantially lower than those reported in earlier efficacy trials of participatory women’s groups in India. 45 Employing incentivised ASHAs and ASHA facilitators as well as building these frontline workers’ capacity through on-the-job-training reduced costs at scale. The intervention covered 1.6 million live births at a cost of INT$9.4 per live birth compared with average cost per live birth of INT$203 (range: 2016 INT$61–INT$537) in efficacy trials.…”
Section: Discussionmentioning
confidence: 99%